FRI0172 THE INFLUENCE OF CALCINEURIN INHIBITORS ON DEVELOPMENT OF CANCER IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS: A RETROSPECTIVE OBSERVATIONAL STUDY IN THE LUNA REGISTRY. (2nd June 2020) - Ichinose, K.; Igawa, T.; Okamoto, M.; Takatani, A.; Yajima, N.; Sada, K. E.; Yoshimi, R.; Shimojima, Y.; Ono, S.; Kajiyama, H.; Sato, S.; Fujiwara, M.; et al.
Abstract : Background: It has been reported that the incidence of cancer in patients with systemic lupus erythematosus (SLE) is higher than that in healthy individuals, but the findings are inconsistent 1 . In the transplantation field, a few studies indicated an association between the use of immunosuppressants and an increased risk of cancer 2 . Calcineurin inhibitors (CNIs), which include cyclosporine and tacrolimus, have been used for >30 years to treat renal and extrarenal manifestations of SLE, but the effects of exposure to CNIs among SLE patients have not been established. Objectives: We investigated the incidence of various cancers (including cervical dysplasia) among SLE patients registered in the LUpus registry of NAtionwide institution (LUNA). We also investigate whether the registrants' exposure to CNIs increased the risk of cancer. Methods: We calculated the standardized incidence ratio (SIR) of cancer among SLE patients based on the age-standardized incidence rate of cancer reported by Japan's Ministry of Health, Labour and Welfare. A multivariate analysis of the risk of cancer was performed using the covariates of age, smoking history, CNI treatment history, maximum steroid dose in the past, and Systemic Lupus International Collaboration Clinics/American College of Rheumatology Damage Index [SDI]) value (excluding the occurrence of cancer) at the time of the patient's registration. Results: We studied 714 patients (663 females; 88.9%).The median age at registry was 44 [interquartile range (IQR): 35–56] years. The median past max. steroid dose was 40 mg/day (IQR: 30–60 mg/day), and the SDI at registration was 1 (IQR 0–2). Smoking history was present in 248 patients (34.9%), and 53 patients (7.4%) experienced cancer complications. Gynecologic malignancies accounted for 71% of all cancers, including 12 cervical dysplasia cases. The standardized incidence rate of cancer in these SLE patients was 1.46 (95%CI: 1.07–1.85, p<0.01). The multivariate analysis showed that a CNI treatment history was not a risk factor for the development of cancer (OR 1.76, 95%CI: 0.63–4.88, p=0.30). After the covariance was adjusted for the propensity score, the risk of cancer in the CNIs group was not increased compared to the non-CNIs group (adjusted OR 2.46, 95%CI: 0.68–8.91, p=0.20). Conclusion: The incidence of cancer in SLE was higher in the LUNA cohort than in the general population. Our results suggest that CNI treatment for individuals with SLE is not a risk factor for the development of cancer. References: [1]Ladouceur A. et.al, Expert Rev Clin Immunol. 2018 Oct;14(10):793-802. [2]Gutierrez-Dalmau A. et.al, Drugs 2007;67(8):1167-98. Disclosure of Interests: None declared